2000
DOI: 10.1002/1529-0131(200003)43:3<568::aid-anr13>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of the effect of obesity in knee osteoarthritis: The mediating role of malalignment

Abstract: BMI was related to OA severity in those with varus knees but not in those with valgus knees. Much of the effect of BMI on the severity of medial tibiofemoral OA was explained by varus malalignment, after controlling for sex. Whether it precedes or follows the onset of disease, varus malalignment is one local factor that may contribute to rendering the knee most vulnerable to the effects of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
184
1
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(207 citation statements)
references
References 35 publications
11
184
1
11
Order By: Relevance
“…This finding indicates that factors beyond BMI may be associated with reports of LE pain in obese children. Lower extremity malalignment is frequently present in obese children [28][29][30]52] and is associated with pain in other populations [45,47,48,64]. Further investigation into factors such as LE alignment that may differ between obese children with pain and those without pain is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicates that factors beyond BMI may be associated with reports of LE pain in obese children. Lower extremity malalignment is frequently present in obese children [28][29][30]52] and is associated with pain in other populations [45,47,48,64]. Further investigation into factors such as LE alignment that may differ between obese children with pain and those without pain is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity-related musculoskeletal comorbidities, including joint pain and lower extremity malalignment, are well characterized among adults [16,17,47]. In adults, increasing body mass index (BMI) and obesity result in knee pain [19], progressive physical disability [5,18], diminished health-related quality of life [18], and a clear risk of development of knee osteoarthritis [7,24,47].…”
Section: Introductionmentioning
confidence: 99%
“…Other hypothesized mechanical-structural hypotheses include increased loading [55], joint misalignment [56][57], structural changes [58], and decreased ambulation and conditioning [37][38] that result from overweight/obesity.…”
Section: Mechanisms: Explaining the Relationship Between Pain And Ovementioning
confidence: 99%
“…Similarly, we found that worsening local valgus alignment is associated with a significantly increased risk of having predominantly lateral disease. Although previous studies have documented significant relationships between alignment and compartment disease [1][2][3][4] , the authors based their determination of alignment on fulllength lower-extremity radiographs. Such radiographs expose the patient to higher amounts of radiation, require greater technical expertise on the part of the radiology technician, and are more expensive than short knee radiographs 5 .…”
mentioning
confidence: 99%
“…In the published studies in which full-length radiographs were used, the knees were frequently categorized, on the basis of absolute values, as normal, with pathological varus, or with pathological valgus [1][2][3][4] . This was done readily because there were already well-established definitions of alignment as measured on full-length radiographs.…”
mentioning
confidence: 99%